Mandibular Angle Implants - Eppley, Barry L. (Facial Plastic Surgery, 2019)
After studying this article, the reader should be able to understand the two basic types of implants for aesthetic augmentation of the jaw angles and the aesthetic goals in using them. The operative steps for surgical placement are described with emphasis on avoiding the common complications of jaw angle implants. The indications for the use of standard versus custom jaw angle implants are also described.
Keywords: jaw angle implant; mandibular angle implants